Exploration of Miidle Age Life Identity Crisis in Novel Midnight Library : A Psychological Perspective - Nasira, Sheila; Natsir, Muhammad (Universitas Negeri Medan, 2024)
This research seeks to analyze how identity crisis is experienced by Nora in the novel Midnight Library. An identity crisis is phenomenon that can happen to someone in their life. The Baumesiter et al theory is applied in this study to examine the kinds, causes and resolution of Nora's identity crisis. Textual analysis was used to carry out as a research design in this research. Textual analysis used for exploring deeper layers of an individual's psychology, including subconscious thinking. By examining speech patterns, textual analysis seeks to comprehend how individuals behave and think. The source of the data is Novel Midnight Library. The data in this research were dialogues and narrations related to the theory in novel “Midnight library” that represent identity crisis through object of the study that is the main character, Nora Seed. The findings show nora experienced the identity deficit type, which is typified by a lack of direction and meaning in life, discontent with one's own accomplishments, and suicidal thoughts. A lot of things caused Nora's identity crisis, including her intense regret for unfulfilled dreams, parental ambivalence, and choosing to live according to the expectations of others rather than her own desires.